Observation of new baryons in the Ξ−bπ+π− and Ξ0bπ+π− systems - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Carus, Leon; Caspary, Rowina; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; et al. (Physical review letters, 2023)
The first observation and study of two new baryonic structures in the final state Ξ0bπ+π− and the confirmation of the Ξb(6100)− state in the Ξ−bπ+π− decay mode are reported using proton-proton collision data collected by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1. In addition, the properties of the known Ξ*0b, Ξ'−b and Ξ*−b resonances are measured with improved precision. The new decay mode of the Ξ0b baryon to the Ξ+c π− π+ π− final state is observed and exploited for the first time in these measurements.
Im Titel ist b tiefgestellt, die 0 hochgestellt
Gesehen am 15.04.2024
LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, L. Carus, R. Caspary, M. De Cian, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, R. Skuza, G. Tuci, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1043 weitere]